Pembangunan Daya Saing Akademik Mahasiswa dalam Era Global dengan Peningkatan Kemampuan Menulis Abstrak Berbahasa Inggris - ., Yugianingrum (Zenit, 2012)
To meet global challenges, Indonesian students have to be prepared to become researchers that will exist in international  scholarly communication, at least by publishing their research in international journals. This paper reports the results of a survey on the knowledge required by undergraduate  students of a medical faculty to write a research paper, specially its abstract, in English. The paper reviews a selection of students’ written questions concerning the knowledge for writing an abstract in English and provides the answers with some information about abstract writing according to international conventions. The results show that the students’ questions are about ways of a) writing a good abstract, b) distinguishing an abstract from an introduction, c) using English correctly in an abstract, d) evaluating a research paper from its abstract, e) choosing the key words, and f) writing a structured abstract. It is recommended that the students should gain more information about  English for academic writing to facilitate their abstract  writing as well as to improve their capacity to compete in the international research paper publication.  Keywords: global challenges, research paper abstract, medical students